2019
DOI: 10.1088/1742-6596/1218/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

Application of Needleman-Wunch Algorithm to identify mutation in DNA sequences of Corona virus

Abstract: Corona virus is a virus capable of mutating very quickly and many other viruses that arise due to mutations of this virus. To find out the location of corona virus mutations of one type to another, DNA sequences can be aligned using the Needleman-Wunsch algorithm. Corona virus data was taken from Genbank National Center for Biotechnology Information from 1985-1992. The Needleman-Wunsch algorithm is a global alignment algorithm in which alignment is performed to all sequences with the complexity of O (mn) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…S1 ). These sequences were compared by global sequence alignment ( www.ebi.ac.uk/Tools/psa/ ) “for two sequences” using Needleman-Wunsch algorithm [ 29 ]. The two amino sequences of 201 residues of SGp RBD of Omicron and WT aligned for pairwise sequence alignment scoring gap penalty of 10.0 with similarity (180/201) and identity (175/201) is 89.6% and 87.1%, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1 ). These sequences were compared by global sequence alignment ( www.ebi.ac.uk/Tools/psa/ ) “for two sequences” using Needleman-Wunsch algorithm [ 29 ]. The two amino sequences of 201 residues of SGp RBD of Omicron and WT aligned for pairwise sequence alignment scoring gap penalty of 10.0 with similarity (180/201) and identity (175/201) is 89.6% and 87.1%, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The alignment arrays for global alignment are analyzed. Table (6) lists the numbers of unique and repeated alignment arrays. Evidently, no repeated alignment arrays are found for global alignment because all the input DNA letters are fully represented in the alignment array.…”
Section: Proposed Algorithmmentioning
confidence: 99%
“…Consequently, producing timely results for large-scale problems requires more efficient algorithms and the use of parallel computing algorithms. PWSA can be used to identify the location of mutations between two viruses (e.g., coronaviruses), and this location can be used as a reference for the manufacture of coronavirus vaccines [6].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some researchers presented an effective model for determining mutation locations in the DNA sequences of this coronavirus [26]. Desautels et al [27] suggested a machine learning-based prediction model of antibody structures qualified for attacking the COVID-19 receptor-binding domain.…”
Section: Introductionmentioning
confidence: 99%